Review of solar crop drying efficiency and its interconnection with meteorological factors - Mfanafuthi Mthandeni Mkhize (Discover Energy)
Abstract This study presents a comprehensive review of key performance parameters influencing solar crop dryers (SCDs), including air velocity, temperature, relative humidity (RH), drying rate, final moisture content, and thermal efficiency. An analysis of over 50 systems, 91% of which employed natural convection in indirect or mixed-mode configurations, revealed efficiency levels typically ranging from 20 to 30%. Several performance gaps were identified, notably the absence of optimised air velocity models, an imbalanced velocity-to-heat ratio, and suboptimal inlet-to-outlet chamber area ratios. Moreover, four major operational challenges were identified: maintaining high drying air temperatures, optimising airflow for moisture removal, managing intermittent thermal energy, and bridging the performance gap between conventional and unconventional designs. It was found that drying air velocity should be varied throughout the drying phases, higher during the constant rate period and lower during the falling rate period to balance heat retention and moisture extraction effectively. Drying rates are instrumental performance indicators, and high values are prevalent in active systems and high-heat-input systems, such as mixed-mode SCDs. Systems with a smaller collector-to-chamber surface area exhibited poor thermal regulation, while divergent inlet-to-outlet chamber areas were shown to mitigate airflow-related temperature losses. Forced convection was observed to enhance airflow and efficiency (up to 70.2%) when supported by proportional thermal input, whereas natural convection systems achieved efficiencies up to 49.5%. Ambient temperature and RH significantly influenced drying rates, with lower RH and higher ambient temperatures being favourable. Enhanced configurations, particularly mixed-mode and indirect SCDs integrated with thermal energy storage (TES) or hybrid heating sources, demonstrated improved thermal stability and energy utilisation. These findings highlight the importance of airflow-heat optimisation and system hybridisation for consistent and efficient SCD operation.